2017
DOI: 10.1007/s12020-017-1495-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone on thyroid function are mediated by type 2 iodothyronine deiodinase in humans

Abstract: GH increased serum fT3 level and decreased serum fT4 level in humans. Our results suggest that its mechanism involves D2 upregulation. Considering this GH effect on thyroid hormone metabolism, data on thyroid function could be useful in the management of GH deficiency and acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…There is an important relationship between the GH-IGF-1 axis and obesity [8][9][10]40], and circulating GH modulates the thyroid axis. Circulating GH levels increased serum FT3 and decreased serum FT4 in humans [41]. Treatment with GH in adults with GH deficiency causes variable changes in thyroid function, the most consistent effect being decreased circulating thyroxine levels [42].…”
Section: Discussionmentioning
confidence: 98%
“…There is an important relationship between the GH-IGF-1 axis and obesity [8][9][10]40], and circulating GH modulates the thyroid axis. Circulating GH levels increased serum FT3 and decreased serum FT4 in humans [41]. Treatment with GH in adults with GH deficiency causes variable changes in thyroid function, the most consistent effect being decreased circulating thyroxine levels [42].…”
Section: Discussionmentioning
confidence: 98%
“…Thyroid hormones act at many sites from the hypothalamic control of GH release to the tissue expression of IGF-1 [ 44 ]. Circulating GH levels increased serum free triiodothyronine and decreased serum FT4 in humans [ 45 ]. GH replacement therapy in adult subjects with GH deficiency syndrome causes different alterations in thyroid function, the most common being the decrease in circulating thyroxine levels [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effects of GH treatment on thyroid function in patients with GH deficiency and hypopituitarism (Glynn et al, ; Losa et al, ; Porretti et al, ). The effects of GH treatment on thyroid gland functions could be understood as the modulatory effect of GH treatment on transmission of fT4 to T3 or reverse T3 in peripheral tissues, the inhibition of TSH due to an increase in somatostatinergic tonus by IGF‐1, and the negative feedback on pituitary gland due to increased T3 production (Yamauchi et al, ). A limited number of investigations have been conducted to detect the effect of GH treatment on thyroid function in patients with PWS.…”
Section: Discussionmentioning
confidence: 99%